2009
DOI: 10.1155/2009/965062
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Clearance Patterns in Normal Older Adults as Documented with Videofluoroscopic Esophagram

Abstract: Normal esophageal bolus transport in asymptomatic healthy older adults has not been well defined, potentially leading to ambiguity in differentiating esophageal swallowing patterns of dysphagic and healthy individuals. This pilot study of 24 young (45–64 years) and old (65+years) men and women was designed to assess radiographic esophageal bolus movement patterns in healthy adults using videofluoroscopic recording. Healthy, asymptomatic adults underwent videofluoroscopic esophagram to evaluate for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
4
31
0
Order By: Relevance
“…1b) [10]. The location of intraesophageal stasis, which is defined by non-specific impaired esophageal mobility [10], was further determined using videofluorography as follows; esophagus was anatomically divided into three sections: (1) cervical esophagus (proximal to the clavicles), (2) aortic esophagus (from the clavicles distal to the aortic arch), and (3) thoracic esophagus (from the bottom of the aortic arch to the lower esophageal sphincter).…”
Section: Videofluorographymentioning
confidence: 99%
“…1b) [10]. The location of intraesophageal stasis, which is defined by non-specific impaired esophageal mobility [10], was further determined using videofluorography as follows; esophagus was anatomically divided into three sections: (1) cervical esophagus (proximal to the clavicles), (2) aortic esophagus (from the clavicles distal to the aortic arch), and (3) thoracic esophagus (from the bottom of the aortic arch to the lower esophageal sphincter).…”
Section: Videofluorographymentioning
confidence: 99%
“…4 Age-related changes in swallowing, including esophageal function, are also well documented. [6][7][8][9] On videofluoroscopy, increased intraesophageal stasis is seen with increasing age. 7,8 Manometric studies have shown a reduction in pressure at the lower esophageal sphincter (LES), upper esophageal sphincter (UES), and reduction in peristaltic wave amplitude and velocity with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] On videofluoroscopy, increased intraesophageal stasis is seen with increasing age. 7,8 Manometric studies have shown a reduction in pressure at the lower esophageal sphincter (LES), upper esophageal sphincter (UES), and reduction in peristaltic wave amplitude and velocity with increasing age. 8 Interactions between the oropharynx and esophagus are poorly understood but frequently observed.…”
Section: Introductionmentioning
confidence: 99%
“…Transport is successful when minimal bolus material is retained within the esophageal body. Traditionally, videofluoroscopy has been the gold standard for examining esophageal bolus transit, 1,2 while more recently multichannel impedance monitoring, combined with manometry, has been introduced to measure bolus transit by detecting changes in resistance to current flow when a bolus traverses an electrode pair. 3,4 Several investigators have studied the predictive value of combined impedance and manometry for bolus transit.…”
Section: Introductionmentioning
confidence: 99%